Integrating Systematic Literature Review and Longitudinal Analysis for Employee Satisfaction Evaluation: A Hospitality Industry Case Study - I Made Sudana; Endah Sudarmilah; Yusuf Sulistyo Nugroho (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The success of service quality in organizations is heavily influenced by employee satisfaction. This research proposes an integrated framework combining a Systematic Literature Review (SLR) with a longitudinal analysis of Employee Satisfaction Survey (ESS) data at Zest Parang Raja Solo to evaluate determinants of job satisfaction over the 2022–2025 period. Following the PRISMA 2020 protocol across 35 selected studies, seven key variables were identified, with leadership emerging as the most dominant factor (74.29%) in global literature. Empirical validation through longitudinal analysis of a qualified total population (N=70 respondents over four years, adhering to strict organizational tenure SOPs) reveals a degrading satisfaction trend, decreasing from 91.99% in 2022 to 85.66% in 2025. This decline was primarily driven by a significant divergence in compensation and workplace facilities, with the